2021
DOI: 10.1186/s42238-021-00082-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of soil microbiota manipulation on secondary metabolites production in cannabis

Abstract: Background Cannabis growing practices and particularly indoor cultivation conditions have a great influence on the production of cannabinoids. Plant-associated microbes may affect nutrient acquisition by the plant. However, beneficial microbes influencing cannabinoid biosynthesis remain largely unexplored and unexploited in cannabis production. Objective To summarize study outcomes on bacterial and fungal communities associated with cannabis using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 114 publications
1
9
0
Order By: Relevance
“… Zielonka et al (2021) reported as most common AMF species associated with industrial hemp various species of the genus Funneliformis , such as F. mosseae , F. caledonium and F. geosporum . Due to its forbidden nature of cannabis in the past, scientific knowledge on microbial diversity in cannabis cultivation, and especially that of variants for recreational or medicinal purposes, is limited ( Ahmed and Hijri, 2021 ). To the best of our knowledge our study is the first to demonstrate effects of the mycorrhizal symbiosis on the production of cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Zielonka et al (2021) reported as most common AMF species associated with industrial hemp various species of the genus Funneliformis , such as F. mosseae , F. caledonium and F. geosporum . Due to its forbidden nature of cannabis in the past, scientific knowledge on microbial diversity in cannabis cultivation, and especially that of variants for recreational or medicinal purposes, is limited ( Ahmed and Hijri, 2021 ). To the best of our knowledge our study is the first to demonstrate effects of the mycorrhizal symbiosis on the production of cannabinoids.…”
Section: Discussionmentioning
confidence: 99%
“…They also improve plant tolerance to a variety of stresses including salinity, herbivory, plant diseases, and heavy-metal pollution ( Ahanger et al, 2014 ; Salam et al, 2017 ). Due to these beneficial features, AMF are a good candidate for acquiring more nutrients and water for plants under conditions where those resources are limited, and hence likely increase plant biomass and the production of these cannabinoids ( Ahmed and Hijri, 2021 ). Beneficial effects of AMF on performance of C. sativa were reported by Citterio et al (2005 ; enhanced performance in heavy-metal polluted soil) and Kakabouki et al (2021a ; biomass and nitrogen and phosphorus content).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial suspension (or microbial inoculum) was prepared from soil collected from the Gault Nature Reserve at Mont Saint-Hilaire. Undisturbed and old maple forests are well known as a potential source of beneficial microbes for crop plants [ 24 ]. Soil samples were taken in four distinct locations, pooled, and homogenized to form a composite sample which was then transported to the lab.…”
Section: Methodsmentioning
confidence: 99%
“…Root-associated microbes have been shown to improve the systematically induced root exudation of metabolites process and affect root transcriptome and metabolome ( Korenblum et al, 2020 ). Manipulation of plant microbiota thus trigger host biosynthetic and signaling pathways ( Berg et al, 2016 ; Pascale et al, 2019 ) and brings up opportunities for plant fitness, improved nutrient usage efficiency, and higher crop yields while limiting chemical fertilizers and greenhouse gas emissions in a sustainable manner ( Adesemoye et al, 2009 ; Berg, 2009 ; Singh and Trivedi, 2017 ; Ahmed and Hijri, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given their potential for positively influencing agricultural productivity, understanding the role of these microbes could enhance our ability to exploit activities that promote efficient soil nutrient use to increase crop yield and quality, while reducing the environmental footprint of agriculture. Given the extraordinary number of microbes that exist in soil and their functional diversity, they could not be examined in depth prior to recent advances in high-throughput sequencing technologies and bioinformatics ( Ahmed and Hijri, 2021 ), that allow to generate a huge amount of sequencing data whose analyses provide an exhaustive taxonomic profile, relative abundance as well as predition of functions. In this study, we used MiSeq amplicon sequencing targeting ribosomal DNA (rDNA) of bacterial 16S and fungal ITS to uncover diversity of roots and rhizosphere soils associated with hemp grown in six different fields located in New York State (United States).…”
Section: Introductionmentioning
confidence: 99%